Ulcerative colitis and concomitant arterial hypertension (literature review) - Khairnasova , Alina (The Ukrainian Scientific Medical Youth Journal, 2024)
ulcerative colitis is a complex disease that results from a complex interaction of genetic predisposition, environmental factors, which leads to dysregulation of the immune system, chronic intestinal inflammation with damage to the mucous membrane. Systemic chronic inflammation can cause the development of arterial hypertension, thereby complicating the course of the primary disease. However, the cause-and-effect relationship between these diseases is not fully understood. Early detection of high blood pressure in patients with ulcerative colitis, a multidisciplinary approach to diagnosis makes it possible to achieve optimal treatment results in a timely manner and prevent the occurrence of intestinal complications. The aim of this study was to provide a comprehensive review of diagnostic procedures such as colonoscopy, inflammatory biomarkers (faecal calprotectin, faecal lactoferrin, serum zonulin), and to study the features of the colon structure in ultrasound diagnostics in patients with ulcerative colitis and concomitant hypertension. The data from PubMed and Ukrainian scientific sources on the comorbidity of these diseases, the possibility of using non-invasive diagnostic methods to assess the condition of the intestine in patients with ulcerative colitis and arterial hypertension were analysed. The literature review includes 50 scientific sources. The main focus is on the pathophysiological relationships of diseases, peculiarities of non-invasive diagnosis of ulcerative colitis during follow-up and early detection of arterial hypertension, which makes it possible to prevent complications in ulcerative colitis. Given the literature review, it can be concluded that the problem of timely diagnosis of hypertension in patients with ulcerative colitis is relevant today. For a rational approach to the management of patients with ulcerative colitis and concomitant hypertension, it is necessary to carry out a set of diagnostic procedures, including outpatient blood pressure measurement, ultrasound examination of the intestinal wall, and the use of non-invasive inflammatory biomarkers.